2023
DOI: 10.1021/acsami.3c06471
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Engineering of VS4 Microspheres as High-Performance Cathodes for Hybrid Mg2+/Li+ Batteries

Abstract: V-based sulfides are considered as potential cathode materials for Mg2+/Li+ hybrid ion batteries (MLIBs) due to their high theoretical specific capacities, unique crystal structure, and flexible valence adjustability. However, the formation of irreversible polysulfides, poor cycling performance, and severe structural collapse at high current densities impede their further development. Herein, VS4 microspheres with various controllable nanoarchitectures were successfully constructed via a facile solvothermal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The chemical composition and surface valence states of the VS 2 /NiS 2 sample were characterized by X-ray photoelectron spectroscopy (XPS). The strong peaks at about 516.4 and 523.9 eV in Figure S2b are attributed to V 4+ in V 2p 3/2 and V 2p 1/2 , respectively. It is worth noting that no other valence states of V were detected. In the Ni 2p spectrum (Figure S2c), the distinct peaks situated at 854.2 and 871.4 eV are ascribed to Ni 2+ 2p 3/2 and Ni 2+ 2p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The chemical composition and surface valence states of the VS 2 /NiS 2 sample were characterized by X-ray photoelectron spectroscopy (XPS). The strong peaks at about 516.4 and 523.9 eV in Figure S2b are attributed to V 4+ in V 2p 3/2 and V 2p 1/2 , respectively. It is worth noting that no other valence states of V were detected. In the Ni 2p spectrum (Figure S2c), the distinct peaks situated at 854.2 and 871.4 eV are ascribed to Ni 2+ 2p 3/2 and Ni 2+ 2p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Impressively, the diffraction peaks of the as-prepared VS 2 @C are distinctly different from those of 2H-VS 2 (JCPDS 89–1640). , Two obviously formed sharp peaks at 2θ = 9.0° and 17.9° corresponding to the interlayer spacing of 0.98 and 0.50 nm can be observed, which can be indexed to the expanded (001) and (002) planes of VS 2 , respectively. , Notably, three diffraction peaks at 35.7°, 45.2°, and 57.1° can be well assigned to (011), (012), and (110) planes of 2H-VS 2 , suggesting that for the three samples the atomic arrangement along above basal planes are the same as 2H-VS 2 . Moreover, it has been reported that the carbonization of carbon source (such as AA and glucose) results in the formation of amorphous carbon layers in the solvothermal process, which can be in situ coated on the surface of the VS 2 nanosheets to enhance the interaction between VS 2 and carbon. However, the characteristic peaks of carbon are not obvious in the XRD patterns, which probably is amorphous and deserves further discussion. When AA is not added in the solvothermal process, the E-VS 2 -200 shows the same XRD pattern as the above three samples, indicating that AA has no influence on the phase structure of VS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous articles have reported that the formation of amorphous carbon layers is due to the carbonization of carbon source (such as AA and glucose) in the solvothermal reaction. 45,46 The higher relative intensity ratio value of D and G bands in amorphous carbon can be calculated to be 0.72, which is beneficial for improving the ion storage properties. 32 TG analysis in air atmosphere was performed to quantify the content of amorphous carbon in the E-VS 2 @C-200 (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…The cycling stability of MLIBs is an important indication of the effectiveness of cathode material modification, which is also an important criterion for practical application in production. The cycling performance of MLIBs was compared with that reported in ref ,, . The relevant comparison results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, it was dissolved in N -methyl pyrrolidone as a binder and uniformly coated onto pure copper foil (99.9%, Goodfellow), achieving a loading of approximately 0.8 mg per cathode. The anode was composed of meticulously polished magnesium foil, while the electrolyte for MILBs consisted of a mixed solvent containing 0.4 M Alkylpyrrolidinium chloride and 0.4 M lithium chloride (LiCl) dissolved in tetrahydrofuran. The MLIBs were assembled under ultrahigh purity conditions within a glovebox where water and oxygen levels were maintained below 0.1 ppm. The galvanostatic cycling and rate capability assessments were systematically carried out on a multichannel battery testing platform.…”
Section: Methodsmentioning
confidence: 99%